Gangguan bunyi Melayu dalam sebutan Arab: satu analisis ringkas - Abdul Jabar, Mohd Azidan (Universiti Putra Malaysia Press, 2004)
Arabic has a wide distribution in the world. There are, apart from the native speakers of Arabic, a hundred million people using Arabic for different reasons. The contact with Malay language and culture can be a source of errors in the use of Arabic by a bilingual subject or by someone learning Arabic as a Second Language (ASL) or Arabic as a Foreign Language (AFL). It may affect all levels of language. This phenomenon is called "interference". Interference may be viewed as the transference of elements of one language to another at various levels including phonological aspects. Based on this assumption, this article attempts to describe forms and types of Malay sound interference in the use of Arabic by the native speakers of Malay.